2016
DOI: 10.30651/must.v1i1.96
|View full text |Cite
|
Sign up to set email alerts
|

Pengembangan Perangkat Pembelajaran untuk Meningkatkan Kemampuan Pemecahan Masalah Matematis Siswa SMP Negeri 12 Pematangsiantar

Abstract: ABSTRAKTujuan dari penelitian ini untuk mengetahui: (1) Bagaimana kualitas perangkat pembelajaran yang dikembangkan dengan model pembelajaran berdasarkan masalah untuk meningkatkan kemampuan pemecahan masalah matematis siswa, dan (2) Bagaimana peningkatan kemampuan pemecahan masalah matematis siswa dengan menggunakan perangkat pembelajaran yang dikembangkan. Perangkat pembelajaran yang dikembangkan adalah buku guru, buku siswa, RPP, LAS, dan instrumen tes kemampuan pemecahan masalah. Populasi dalam penelitian … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0
12

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 1 publication
0
5
0
12
Order By: Relevance
“…Sulistyoningsih (2015) mengutarakan keterampilan berpengaruh positif terhadap pemecahan masalah. Dari pendapat Simanungkalit (2015), keterampilan yang dimiliki siswa dapat diterapkan untuk memecahkan masalah yang bersifat tidak rutin. Kurangnya keterampilan ini yang menyebabkan subjek penelitian tidak mampu menyelesaikan soal dengan tepat, hal ini disebabkan oleh: a. Kesalahan yang disebabkan kesalahan data yang digunakan dari proses sebelumnya yaitu memahami dan merencanakan.…”
Section: Skill Errors (Kesalahan Keterampilan)unclassified
“…Sulistyoningsih (2015) mengutarakan keterampilan berpengaruh positif terhadap pemecahan masalah. Dari pendapat Simanungkalit (2015), keterampilan yang dimiliki siswa dapat diterapkan untuk memecahkan masalah yang bersifat tidak rutin. Kurangnya keterampilan ini yang menyebabkan subjek penelitian tidak mampu menyelesaikan soal dengan tepat, hal ini disebabkan oleh: a. Kesalahan yang disebabkan kesalahan data yang digunakan dari proses sebelumnya yaitu memahami dan merencanakan.…”
Section: Skill Errors (Kesalahan Keterampilan)unclassified
“…The development of mathematics handouts should be tailored to the needs and characteristics of students. This is reinforced by Rick Hunter Simanungkalit who says that the development of learning devices that do not fit the needs and characteristics of students will have an impact on the learning stages of students (Simanungkalit, 2016). The reason for the importance of developing mathematics handouts is the availability of materials in accordance with the demands of the curriculum, target characteristics, and the demands of solving learning problems.…”
Section: Introductionmentioning
confidence: 99%
“…In line with (Kawiyah, 2015), it is shown that the development of scientific-based mathematics learning tools to improve student learning outcomes is considered effective for use with the percentage of students achieving KKM of more than 75%. Research also shows that the results of effectiveness testing on learning tools to improve student learning outcomes are considered effective with completeness of student learning outcomes of 75% (Simanungkalit, 2016). The researcher then conducted an average difference test to see the difference in the ability to solve mathematical problems of the experimental class and the control class.…”
Section: Figure 1 Lkpd Cover 132mentioning
confidence: 99%